Foreign Influences on Nordic (Noir) Borderlands - Marklund, Anders (European Journal of Scandinavian Studies, 2019)
This article analyses the three recent Nordic Noir television series Bordertown (Sorjonen) from Finland, Trapped (Ófæro), from Iceland, and the Danish- Swedish The Bridge (Broen/Bron). All series are located on national borderlands, and this article aims to discern the significance of using such borderland settings. Departing from Doreen Massey's emphasis on places as being inherently interlinked with other places, the article characterises the various ways foreign influences are represented and narrativised in these three series.